2020
DOI: 10.21203/rs.3.rs-45694/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Circular RNA circZFR Phosphorylates Rb Promoting Cervical Cancer Progression by Regulating the SSBP1/CDK2/cyclin E1 Complex

Abstract: Background: As a novel type of non-coding RNA, circular RNAs (circRNAs) play a critical role in the initiation and development of various diseases, including cancer. However, the exact function of circRNAs in human cervical cancer remains largely unknown. Methods: We identified the circRNA signature of upregulated circRNAs between cervical cancer and paired adjacent normal tissues. Using two different cohorts and GEO database, a total of six upregulated circRNAs were identified with a fold change >2, and P … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The activated complex phosphorylates p-Rb and interrupts its pairing with E2F1. Subsequently, the released E2F1 transcription factor promotes the G1/S transition and the proliferation of CC cells after it triggers the transcription of genes associated with target DNA replication (Zhou et al 2021).…”
Section: Cervical Cancermentioning
confidence: 99%
“…The activated complex phosphorylates p-Rb and interrupts its pairing with E2F1. Subsequently, the released E2F1 transcription factor promotes the G1/S transition and the proliferation of CC cells after it triggers the transcription of genes associated with target DNA replication (Zhou et al 2021).…”
Section: Cervical Cancermentioning
confidence: 99%
“…They can form an SSBP1-circZFR complex that activates the CDK2/cyclin-E1 complex to induce p-Rb phosphorylation, thereby releasing the E2F1 transcription factor. Therefore, this promotes the progression of the CC cell cycle and induces the proliferation of CC cells ( Zhou et al, 2021 ). In another study, circCDKN2B-AS1 promoted the aerobic glycolysis of CC cells by recruiting IM3 protein, which is also a kind of RBP, to regulate the stability of the rate-limiting enzyme Hexokinase 2 (HK2) mRNA in the aerobic glycolysis pathway.…”
Section: Mechanism Of Circrna In Cervical Cancermentioning
confidence: 99%
“…ROC analysis showed that the AUC of circ_0018289 was 0.907 ( He et al, 2020 ), the AUC of hsa_circ_0107593 was 0.869 ( Liao et al, 2020 ), and the AUC of circZFR was 0.88, which could significantly separate tumor tissue from ANT. Moreover, the clinical pathological features of 40 patients with CC revealed a positive correlation between circZFR expression and lymphatic metastasis, Ki67 values, and squamous cell carcinoma antigen (SCC Ag) value ( Zhou et al, 2021 ). So circ_0018289, hsa_circ_0107593, and circZFR can also serve as potential disease monitoring biomarkers of CC.…”
Section: Application Of Circrna In Clinical Research Of Cervical Cancmentioning
confidence: 99%
“…Analogously, circ_0000376 has also been found to serve as a competitive endogenous RNA (ceRNA) of miR‐1182 to accelerate migration, invasion, and glycolysis through upregulating NOVA2 in NSCLC 13 . Circ_0072088, a well‐known circRNA originating from zinc finger RNA binding protein (ZFR), has been verified to be a carcinogenic factor in cervical and esophageal squamous cell cancers 14,15 . It has also been reported that the upregulation of circ_0072088 might contribute to pancreatic ductal adenocarcinoma cell glycolysis in vitro 16 .…”
Section: Introductionmentioning
confidence: 97%
“…13 Circ_0072088, a well-known circRNA originating from zinc finger RNA binding protein (ZFR), has been verified to be a carcinogenic factor in cervical and esophageal squamous cell cancers. 14,15 It has also been reported that the upregulation of circ_0072088 might contribute to pancreatic ductal adenocarcinoma cell glycolysis in vitro. 16 Furthermore, recent evidence indicated that circ_0072088 could facilitate NSCLC development by increasing cell growth and metastasis.…”
Section: Introductionmentioning
confidence: 97%